A review of Luxiaria Walker and its allied genus Calletaera Warren (Lepidoptera, Geometridae, Ennominae) from China - Jiang, Nan; Xue, Dayong; Han, Hongxiang (Zootaxa, 2014)
The genus Luxiaria Walker and its allied genus Calletaera Warren in China, including 16 species in all, are reviewed. Five new species are described: C. obvia sp. nov., C. acuticornuta sp. nov., C. rotundicornuta sp. nov., C. dentata sp. nov., C. trigonoprocessus sp. nov. The species L. acutaria (Snellen, 1877) and L. tephrosaria (Moore, 1868) are newly recorded for China. Two new combinations are established: C. obliquata (Moore, 1888) comb. nov. and C. consimilaria (Leech, 1897) comb. nov. Four new synonyms are established: Eutoea Walker, 1860 (= Bithiodes Warren, 1894 syn. nov.); Calletaera Warren, 1895 (=Bithiodes Warren, 1899 syn. nov.), based on the fixation of nominal type Acidalia inexactata Walker, 1861, for the genus name Bithiodes Warren, 1894; L. emphatica Prout, 1925 (= L. costinota Inoue, 1978 syn. nov.); C. subexpressa (Walker, 1861) (= C. digrammata Wehrli, 1925 syn. nov.). Diagnoses for all Chinese species are provided. Illustrations of external features and genitalia are presented.